Association of Retrospective Peer Review and Positive Predictive Value of Magnetic Resonance Imaging-Guided Vacuum-Assisted Needle Biopsies of Breast - Ceren Yalnız; Juliana Rosenblat; David Spak; Wei Wei; Marion Scoggins; Carisa Le-Petross; Mark J Dryden; Beatriz Adrada; Başak E. Doğan (European Journal of Breast Health, 2019)

(untitled)
Objective: To evaluate the association between retrospective peer review of breast magnetic resonance imaging-guided vacuum-assisted needle biopsies and positive predictive value of subsequent magnetic resonance imaging-guided biopsies.Materials and Methods: In January, 2015, a weekly conference was initiated in our institution to evaluate all breast magnetic resonance imagingguided vacuum-assisted needle biopsies performed over January 1, 2014-December 31, 2015. During this weekly conferences, breast dynamic contrastenhanced magnetic resonance imaging findings of 6 anonymized cases were discussed and then the faculty voted on whether they agree with the biopsy indication, accurate sampling and radiology-pathology correlation. We retrospectively reviewed and compared the magnetic resonance imaging indication, benign or malignant pathology rates, lesion types and the positive predictive value of magnetic resonance imaging-guided vacuum-assisted needle biopsy in the years before and after initiating this group peer review.Results: The number of dynamic contrast-enhanced magnetic resonance imaging and magnetic resonance imaging-guided vacuum-assisted needle biopsies before and after initiating the review were 1447 vs 1596 (p=0.0002), and 253 (17.5%) vs 203 (12.7%) (p=0.04), respectively. There was a significant decrease in the number of benign biopsies in 2015 (n=104) compared to 2014 (n=154, p=0.04). The positive predictive value of magnetic resonance imaging-guided biopsy significantly increased after group review was implemented (Positive predictive value in 2014=%39.1 and positive predictive value in 2015=%48.8) (p=0.03), although the indications (p=0.49), history of breast cancer (p=0.14), biopsied magnetic resonance imaging lesion types (p=0.53) were not different. Less surgical excision was performed on magnetic resonance imaging-guided vacuum-assisted needle biopsy identified high-risk lesions in 2015 (p=0.25).Conclusion: Our study showed an association between retrospective peer review of past biopsies and increased positive predictive value of magnetic resonance imaging-guided vacuum-assisted needle biopsies in our institution.